Thoracic ultrasonography as a predictor of pleurodesis success in malignant pleural effusion - Corcoran, J; Hallifax, R; Yousuf, A; Mercer, R; Asciak, R; Hassan, M; Psallidas, I; Rahman, N (BMJ Publishing Group, 2017)
Malignant pleural effusion (MPE) is common with 1 new case annually for every 2,000 individuals, imposing a significant burden on patients and healthcare providers as a result. Most patients require definitive treatment, usually drainage and chemical pleurodesis, to relieve symptoms and prevent fluid recurrence. Pleurodesis is reported to have a success rate of around 70%, with no robust means of predicting which patients will suffer failure of the procedure. Thoracic ultrasound (TUS) has been shown to be capable of identifying the presence of pleural adhesions in other clinical scenarios, and could therefore have a role in predicting long-term pleurodesis success or failure in MPE.